Efficient OER Catalysts: Efficient OER Catalyst with Low Ir Volume Density Obtained by Homogeneous Deposition of Iridium Oxide Nanoparticles on Macroporous Antimony‐Doped Tin Oxide Support (Adv. Funct. Mater. 1/2020). (3rd January 2020) - Böhm, Daniel; Beetz, Michael; Schuster, Maximilian; Peters, Kristina; Hufnagel, Alexander G.; Döblinger, Markus; Böller, Bernhard; Bein, Thomas; Fattakhova‐Rohlfing, Dina
Abstract : In article number 1906670, Daniel Böhm, Dina Fattakhova‐Rohlfing, and co‐workers present a novel scalable approach for the design of a dimensionally stable iridium‐based oxygen evolution reaction (OER) catalyst architecture with a very low iridium volumetric loading density but very high OER activity, achieved by conformal deposition of ultrasmall IrO2 nanoparticles on porous microparticles serving as the catalyst support. Cover image designed by Christoph Hohmann, Munich Center for Quantum Science and Technology.